Thermodynamic Calculation among Cerium, Oxygen, and Sulfur in Liquid Iron - Pan, Fei (Sci Rep, 2016)
Thermodynamic calculation has been applied to predict the inclusion formation in molten SS400 steel. When the Cerium addition in liquid iron is 70 ppm and the initial Oxygen and Sulphur are both 110 ppm, the formation of oxides containing Cerium would experience the transformation from Ce(2)O(3) to CeO(2) and also the formation of sulfides containing Cerium would experience the transformation from CeS to Ce(2)S(3) and then to Ce(3)S(4). Below 2000 K the most thermodynamic stable matter is CeO(2) and the less thermodynamic stable inclusion is CeS. Only when the amount of [O] is extremely low and the amount of [S] and [Ce] is relatively high, Ce(2)S(3) has the possibility to form.